Multi‐trophic guilds respond differently to changing elevation in a subtropical forest. Issue 6 (17th November 2017) - Binkenstein, Julia; Klein, Alexandra‐Maria; Assmann, Thorsten; Buscot, François; Erfmeier, Alexandra; Ma, Keping; Pietsch, Katherina A.; Schmidt, Karsten; Scholten, Thomas; Wubet, Tesfaye; Bruelheide, Helge; Schuldt, Andreas; et al.
Abstract : Negative relationships between species richness and elevation are common and attributed to changes in single environmental properties associated to elevation, such as temperature and habitat area. However, research has lacked taxonomic breadth and comprehensive elevation studies that consider multiple groups from different trophic levels are rare. We thus analysed 24 groups of plants, arthropods, and microorganisms grouped into six trophic guilds (predators, detritivores, herbivores, plants, bacteria and fungi) along a relatively short elevational gradient ( 600 m) in a subtropical forest in south‐east China. The total species richness of all organisms was not related to elevation, nor was the richness of plants, herbivores or microorganisms. However, species richness and abundance in two major trophic guilds of arthropods changed with elevation, which was mediated by changes in elevation‐associated habitat properties. Specifically, deadwood mass increased with elevation, which increased detritivore richness indirectly via detritivore abundance, thus supporting the 'more individuals hypothesis'. In contrast, lower predator richness at higher elevations was directly related to lower mean temperatures, which had no effect on abundance. Our study demonstrates that even along relatively short gradients, elevation can have strong direct and abundance‐mediated effects on species richness, but with effects varying from positive to negative signs depending on local resource availability and the characteristics of groups or trophic guilds. If elevation positively influences local environmental properties that benefit a given group, richness can increase towards higher elevations. Thus, the effect of global change in mountainous regions should be evaluated within the local environmental context using multi‐taxon approaches.